Analysis of Changes in Antibiotic Use Patterns in Korean Hospitals during the COVID-19 Pandemic - Bongyoung Kim; Hyeonjun Hwang; Jungmi Chae; Yun Seop Kim; Dong-Sook Kim (Antibiotics, 2023)
With the onset of the coronavirus disease 2019 (COVID-19) pandemic, changes in patient care and antibiotic use have occurred in hospitals. The data of the National Health Insurance System’s claims of inpatients from all hospitals in Korea between January 2019 and December 2020 were obtained from the Health Insurance Review & Assessment Service and analyzed. The trend in the use of all antibacterial agents in both hospitals declined for the total number of COVID-19 patients at the bottom 10% and those in the top 10%. Specifically, a decreasing trend in the use of broad-spectrum antibacterial agents predominantly prescribed for community-acquired cases and narrow-spectrum beta-lactam agents were observed in both hospitals. In the aftermath of the COVID-19 pandemic, the total use of antibacterial agents has gradually decreased among patients with pneumonia and those with severe COVID-19. In contrast, its use has increased gradually among those with mild to moderate COVID-19. A decreasing trend in overall antibiotic use was observed during the COVID-19 pandemic, and an increasing trend in antibiotic use was observed in patients with mild to moderate COVID-19 in Korean hospitals.